PERMASALAHAN GURU DALAM PENGGUNAAN TEKNOLOGI PEMBELAJARAN DIGITAL DI SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital era has brought significant transformations to the education sector, particularly in the role of elementary school teachers as learning facilitators. Teachers are required to possess adequate digital literacy skills that align with the demands of modern learning. This is essential for enabling teachers to adapt to the characteristics of students who are part of the digital generation and to integrate technology effectively and creatively into the learning process. However, many teachers still face challenges such as low levels of digital literacy, limited infrastructure, and a lack of motivation and support from the school environment. This study employs a descriptive qualitative method with a literature review approach to analyze the problems faced by teachers in implementing digital learning technologies in elementary schools. The findings indicate that teacher competencies include the ability to design digital learning media, utilize social media, and use search engines to find learning resources. The main issues involve the inability to master digital applications, limited technological facilities, and heavy workloads. Therefore, training, adequate facilities, government support, as well as innovation and collaboration among teachers are needed to enhance the quality of digital learning. Overall, improving teachers’ digital competencies is crucial for creating innovative and high-quality learning processes in the context of digital-era education, ultimately contributing to the advancement of primary education quality.